Dimensions of the anti-austerity movement in Spanish society and politics: a governmental approach - Dimitriou, Giorgos (The Greek Review of Social Research, 2023)
Just like in Greece, in Spain the decade 2010-2019 was productive in both political and social movements. My aim is to summarise the basic features of the Spanish anti-austerity movement, with a parallel assessment of its achievements. In addition, I am also referring to the usual criticism against the political strategies of Podemos and the municipalist platforms that emanated from the 15M movement. From the contestation of the postpolitical Transition regime (Transicón), all the way through the relational, caring and feminising political alternatives (put forward by the strategies of the new municipalism) are emerging useful experiences for the construction of a new homo politicus, through inclusive and participatory governmental techniques. The concept of governmentality will help me specify the reasons why the demands for democratisation remain today equally relevant and multileveled.